A sealing glass blank for power lithium battery and preparation method thereof

By adjusting the oxide ratio and preparation process, sealed glass blanks for power lithium batteries with high density and high thermal expansion coefficient were prepared, which solved the problems of low density, easy hydrolysis of phosphate glass and insufficient thermal expansion coefficient in the prior art. Significantly improves sealing and insulation properties.

CN117682759BActive Publication Date: 2024-12-17CNBM RESEARCH INSTITUTE FOR ADVANCED GLASS MATERIALS GROUP CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202311579438.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-11-24
Publication Date
2024-12-17
Estimated Expiration
2043-11-24

AI Technical Summary

Technical Problem

The existing sealing glass powder for power lithium batteries has low density and high porosity, phosphate glass is easy to hydrolyze, the thermal expansion coefficient is not high enough, and the packaging process is immature, which affects sealing and insulation properties.

Method used

P2O5:30-50%, TeO2:20-50%, ZnO2:8-15%, Li2O:1-10%, Na2O:0-10%, K2O:1-15%, Al2O3:1-10%, Bi2O3: 0.1-14%, CuO: 0-20% oxide ratio, and use injection molding technology to prepare the glass blank by precalcining, mixing, melting, crushing and grinding, injection molding, degumming and vitrification sintering steps. and inert gas atmosphere sintering to improve the density and chemical stability of the glass blank.

Benefits of technology

It improves the thermal expansion coefficient and chemical stability of the glass blank, reduces the softening temperature, enhances the sealing and insulation properties, avoids the hydrolysis of phosphate glass, and improves the product's pass rate and application performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The present invention discloses a sealing glass blank for power lithium battery and a preparation method thereof, belonging to the technical field of glass powder preparation. The melted glass liquid is water quenched and ground into glass powder, then mixed with a suitable binder at a certain temperature, granulated and crushed, and injected on an injection molding machine to obtain a glass blank. The glass blank is then immersed in a solvent for degumming, and finally vitrified and sintered to obtain a sealing glass blank. The sealing glass blank prepared by the method of the present invention has a thermal expansion coefficient of >170×10 ‑7 / ℃, softening point <450℃, with the advantages of high thermal expansion coefficient, low sealing temperature, excellent chemical resistance and low bubble content, which can meet the performance requirements of sealing glass for power lithium battery electrode caps.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of glass powder preparation, and in particular to a sealing glass blank for a power lithium battery and a preparation method thereof. Background Art

[0002] The new energy vehicle industry is one of the emerging industries, and power lithium batteries are the "heart" of new energy vehicles. The packaging materials used for power lithium batteries play a role in isolating the outside air, moisture and internal electrolyte on the one hand, and on the other hand, they play a role in electrical insulation, separating the battery pole and the metal shell to maintain the electrical neutrality of the shell. Unlike ordinary lithium batteries, the operating environment of power lithium batteries is extremely harsh, so the packaging technology requirements are very high. In addition to optimizing the structural design of the sealing parts, the key to power lithium battery electrode packaging technology is to select suitable packaging materials.

[0003] At present, the packaging materials between the pole and the metal shell of power lithium batteries include plastic sealing rings, ceramic metallization materials and sealing glass powder materials. The biggest advantage of glass powder packaging technology is that after packaging, the glass and the oxide film on the metal surface can form a chemical bond, which is conducive to achieving airtight sealing of the glass and excellent electrical insulation. At present, the sealing glass powder used in power lithium batteries mainly includes low-melting point glass systems such as phosphates, vanadates and bismuthates. The sealing glass powder must be made into a glass blank before installation and sintering. The commonly used preparation method for glass blanks is dry pressing, that is, glass powder and organic binder are mixed into slurry, and spray granulation is used to obtain spherical glass granulation powder with a certain density, and then die-casting is performed on a blanking machine.

[0004] At present, there are still several problems after the granulated powder obtained by spray granulation is pressed. First, the density of the glass blank is low (less than 85%) and the porosity is high, which will cause more bubbles to be generated inside the glass during sintering, thereby affecting the insulation and sealing performance of the product; second, if the sealing glass blank for power lithium batteries adopts a phosphate glass system, glass hydrolysis is easy to occur during the preparation of the slurry for spray granulation, which destroys the structure and performance of the sealing glass; third, the thermal expansion coefficient of the existing sealing glass is not high enough and the packaging process is not mature, all of which limit its practical application. Summary of the invention

[0005] In view of the actual problems existing in the current sealing glass powder for power lithium batteries, the present invention discloses a sealing glass blank for power lithium batteries and a preparation method thereof.

[0006] In order to achieve the above object, the technical solution adopted by the present invention is as follows:

[0007] A sealing glass blank for a power lithium battery is made of the following oxides in molar percentage: P2O5: 30-50%, TeO2: 20-50%, ZnO2: 8-15%, Li2O: 1-10%, Na2O: 0-10%, K2O: 1-15%, Al2O3: 1-10%, Bi2O3: 0.1-14%, and CuO: 0-20%.

[0008] Further, it is made of the following oxides in molar percentages, P2O5: 35-45%, TeO2: 25-40%, ZnO2: 8-12%, Li2O: 2-8%, Na2O: 1-7%, K2O: 2-12%, Al2O3: 2-7%, Bi2O3: 2-10%, CuO: 5-15%.

[0009] Furthermore, the sum of the molar percentages of P2O5 and TeO2 is 55%-75%.

[0010] Furthermore, the sum of the molar percentages of Li2O+Na2O+K2O is 10%-20%.

[0011] Furthermore, a method for preparing a sealing glass blank for a power lithium battery comprises the following steps:

[0012] a. Ingredients: According to the above formula, the glass oxide components are converted into the introduced compound raw materials, and the corresponding raw materials are weighed, wherein P2O5 is introduced by sodium dihydrogen phosphate and ammonium dihydrogen phosphate;

[0013] b. Pre-calcination: First, mix the weighed sodium dihydrogen phosphate, ammonium dihydrogen phosphate and zinc peroxide evenly, place them in an electric furnace at 400-500°C for 0.5-1.5 hours, and then cool them to room temperature with the furnace;

[0014] c. Mixing: Mix the weighed remaining raw materials with the pre-calcined sodium dihydrogen phosphate, ammonium dihydrogen phosphate and zinc peroxide mixture, and fully mix the raw materials in a mixer with zirconium balls, mix for 1-3 hours to prepare a mixture;

[0015] d. Melting: Place the crucible in a high-temperature electric furnace, add the mixture, raise the temperature to 850-1100°C according to the step temperature system, and keep it warm for 30-120 minutes to obtain a clear glass liquid;

[0016] e. Crushing and grinding: Roll the molten glass in an open mill to cool it to room temperature, grind it and sieve it;

[0017] f. Injection molding: The sealing glass powder prepared above and the binder are mixed in a mass ratio of (4-5): 1 in an internal mixer, and then pelletized or crushed to form a feed, and then heated and injected on an injection molding machine to obtain a sealing glass green body;

[0018] g. Degumming: The polished sealing glass blank is immersed in a solvent for 3-6 hours for degumming to remove the organic binder;

[0019] h. Vitrification sintering: The debonded sealing glass blank is vitrified and sintered at 350-450°C in an inert gas atmosphere sintering furnace. After keeping warm for 0.5-1.5 hours, it is cooled with the furnace. After sintering, the glass blank shrinks and takes shape, and finally a high-density sealing glass blank is obtained.

[0020] Furthermore, the particle size distribution of the sealing glass powder used in step f is D50: 60-80 μm, D99: 150-180 μm.

[0021] Furthermore, the binder used in step f is an oil-soluble organic binder, which is one or more of ethyl cellulose, povidone, polyvinyl acetate, and polyvinyl acetal.

[0022] Furthermore, the solvent used in step g is one or more of ethanol, ethyl acetate, acetone, chloroform, and xylene.

[0023] Furthermore, the mixing temperature is 170-240° C., the injection temperature is 170-250° C., and the injection pressure is 12-30 MPa.

[0024] The role of each glass component in the formula, the reasons for selecting the content, and the technical principles on which the present invention is based are:

[0025] P2O5 is a glass-forming oxide. It forms a structural network of phosphate glass with phosphorus-oxygen tetrahedron [PO4], but it will reduce the chemical stability of the glass. Excessive P2O5 content will cause phosphate glass to be easily hydrolyzed. The suitable range of P2O5 in the present invention is 30-50%. TeO2 is a glass-forming oxide. The structural units in the glass mainly include tetracoordinated [TeO4] and tricoordinated [TeO3]. It exists in a Te-O-Te chain structure or a more complex fabric network structure. The thermal expansion coefficient of glass with tellurite glass as the main structure is large, but introducing too much will reduce the chemical stability of the glass. The suitable range of TeO2 in the present invention is 20-50%. Alkali metal oxides Li2O, Na2O, and K2O do not participate in the network structure and belong to network exogenous oxides. They play a role in increasing the thermal expansion coefficient of glass and reducing the softening temperature, but the chemical stability of the glass will be impaired. By adjusting the molar percentage of Li2O, Na2O, and K2O, using the alkali metal ion Li + 、Na + , K +The radius difference forms a mixed alkali effect, which is beneficial to the melting of glass and the formation of glass state, and significantly improves the chemical stability of glass. In the present invention, the suitable range of Li2O is 1-10%, the suitable range of Na2O is 0-10%, and the suitable range of K2O is 1-15%. ZnO2 decomposes into zinc oxide at high temperature to become a glass network intermediate oxide, which can reduce the softening point of glass and improve the stability of glass within a certain range. When the content is too little, it is not easy to form glass, and when the content is too high, the glass is easy to crystallize and the softening point increases. In the present invention, the suitable range of ZnO2 is 8-15%.

[0026] Al2O3 is a glass network intermediate oxide, which plays a special role in phosphate glass. Aluminum can form aluminum oxide tetrahedron with double-bonded oxygen in phosphate glass. Due to the formation of [AlPO4] groups in the glass, the original layered (or chain) structure of phosphate is transformed into a frame structure, which effectively improves and strengthens the structure of phosphate glass, and improves thermal stability and chemical stability. However, if too much is introduced, it will cause the viscosity of the glass liquid to increase rapidly, melting becomes difficult, and the thermal expansion coefficient decreases rapidly. The suitable range of Al2O3 in the present invention is 1-10%. Bi2O3 is a glass network generator oxide with a low softening point. After introduction, as the Bi2O3 doping amount increases, Bi 3+ It enters the glass network structure and plays a role in connecting POP, enhancing the tightness of the glass network structure and improving the chemical stability of the glass. However, if the content is too high, it will easily lead to glass crystallization. The suitable range of Bi2O3 in the present invention is 0.1-14%. CuO is an oxide outside the glass network. After introduction, it can effectively reduce the diffusion rate of water molecules in the glass and can also + Produce a "hindrance effect", greatly improving the chemical stability of the glass. In addition, according to the chelation mechanism of polyphosphate, copper ions can be connected between two linear phosphates or between two adjacent phosphorus oxygen tetrahedrons [PO4] of linear phosphates by non-bridging oxygen, thereby increasing the strength of the POP chain in the phosphate glass, stabilizing the structure of the glass and significantly improving the chemical stability of the glass; at the same time, the introduction of copper ions can improve the wettability and sealing strength between glass and metal, but excessive introduction will increase the high-temperature viscosity and crystallization tendency of the glass. The suitable range of CuO in the present invention is 0-20%.

[0027] Beneficial effects of the present invention:

[0028] 1. The sealing glass blank prepared by the present invention has a high thermal expansion coefficient and a low softening temperature. At 300°C, the thermal expansion coefficient is greater than 170×10 -7 / ℃, softening temperature <450℃, which meets the sealing requirements of aluminum / aluminum or aluminum / copper in power lithium battery electrode cover.

[0029] 2. The injection molding technology is used to prepare the sealing glass blank. There is no need to prepare glass powder slurry for spray granulation, which avoids the hydrolysis of phosphate glass. Compared with the traditional method of manufacturing glass blanks, it has the advantages of high density, low bubble content, and excellent chemical stability, which is conducive to improving the performance indicators such as sealing and insulation of the electrode cover. The interior of the glass blank is more uniform, and the qualified rate of products after vitrification sintering is high. DETAILED DESCRIPTION

[0030] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0031] A method for preparing a sealing glass blank for a power lithium battery, the operating steps adopted in the specific embodiment are as follows:

[0032] a. Ingredients: According to the above formula, the glass oxide components are converted into the introduced compound raw materials, and the corresponding raw materials are weighed, wherein P2O5 is introduced by sodium dihydrogen phosphate and ammonium dihydrogen phosphate;

[0033] b. Pre-calcination: First, weigh the sodium dihydrogen phosphate, ammonium dihydrogen phosphate and zinc peroxide and mix them evenly, place them in an electric furnace at 460°C for 1.2 hours, and then cool them to room temperature with the furnace;

[0034] c. Mixing: Mix the weighed remaining raw materials with the pre-calcined sodium dihydrogen phosphate, ammonium dihydrogen phosphate and zinc peroxide mixture, and fully mix the raw materials in a mixer with zirconium balls, mix for 2 hours to prepare a mixture;

[0035] d. Melting: Place the crucible in a high-temperature electric furnace, add the mixture, raise the temperature to 900°C according to the step temperature system, and keep it warm for 90 minutes to obtain a clear glass liquid;

[0036] e. Crushing and grinding: Roll the molten glass in an open mill to cool it to room temperature, grind it and sieve it;

[0037] f. Injection molding: The sealing glass powder prepared above (the particle size distribution of the sealing glass powder is D50: 70 μm, D99: 170 μm) and ethyl cellulose are mixed in a mixer at a mass ratio of 4.5:1, and then granulated to form a feed material, which is then heated and injected on an injection molding machine (injection temperature 210°C, injection pressure 15 MPa) to obtain a sealing glass green body;

[0038] g. Degumming: The polished sealing glass blank is immersed in xylene for 5 hours for degumming to remove the organic binder;

[0039] h. Vitrification sintering: The debonded sealing glass blank is vitrified and sintered at 360°C in an inert gas atmosphere sintering furnace. After keeping warm for 1 hour, it is cooled in the furnace. After sintering, the glass blank shrinks and takes shape, and finally a high-density sealing glass blank is obtained.

[0040] i. Testing: The thermal expansion coefficient, softening temperature, water resistance stability and sealing airtightness of the glass powder are tested respectively. The thermal expansion coefficient of the glass is tested according to GB 16920-2015 "Determination of the Average Linear Thermal Expansion Coefficient of Glass", the softening temperature is tested according to ATSM 1350 "Standard Test Method for Measuring Viscosity of Glass Between Softening Point and Annealing Range", the water resistance stability is tested according to GB / T 6582-1997 "Particle Test Method and Classification of Water Resistance of Glass at 98°C", and the airtightness test method of the sealing part is tested according to Method 112 Experimental Condition C Procedure Ι in GJB360B-2009 "Test Methods for Electronic and Electrical Components".

[0041] Table 1

[0042]

[0043]

[0044] The above is a detailed description of an embodiment of the present invention, but the content is only a preferred embodiment of the present invention and cannot be considered to limit the scope of implementation of the present invention. All equivalent changes and improvements made within the scope of the present invention should still fall within the scope of the patent coverage of the present invention.

Claims

1. A sealing glass blank for a power lithium battery, characterized in that: Examples of molar percentages of oxide components of the sealing glass blank include P2O5: 30-50%, TeO2: 20-50%, ZnO2: 8-15%, Li2O: 1-10%, Na2O: 0-10%, K2O: 1-15%, Al2O3: 1-10%, Bi2O3: 0.1-14%, and CuO: 0-20%.

2. The sealing glass blank for a power lithium battery according to claim 1, characterized in that: Examples of molar percentages of oxide components of the sealing glass blank include P2O5: 35-45%, TeO2: 25-40%, ZnO2: 8-12%, Li2O: 2-8%, Na2O: 1-7%, K2O: 2-12%, Al2O3: 2-7%, Bi2O3: 2-10%, and CuO: 5-15%.

3. The sealing glass blank for a power lithium battery according to claim 1, characterized in that: The sum of the molar percentages of P2O5 and TeO2 is 55%-75%.

4. The sealing glass blank for a power lithium battery according to claim 1, characterized in that: The sum of the molar percentages of Li2O+Na2O+K2O is 10%-20%.

5. A method for preparing a sealing glass blank for a power lithium battery according to claim 1, characterized in that: The method is achieved through the following process steps: (1) Ingredients: convert the glass oxide components into the introduced raw materials according to the molar percentage of the oxide components of the sealing glass blank as described in claim 1, and weigh the corresponding raw materials, wherein P2O5 is introduced through sodium dihydrogen phosphate and ammonium dihydrogen phosphate; (2) Pre-calcination: First, mix the weighed sodium dihydrogen phosphate, ammonium dihydrogen phosphate and zinc peroxide evenly, place them in an electric furnace and react at 400-500°C for 0.5-1.5 hours, then cool them to room temperature with the furnace; (3) Mixing: Mix the weighed remaining raw materials with the pre-calcined mixture of sodium dihydrogen phosphate, ammonium dihydrogen phosphate and zinc peroxide, and fully mix the raw materials in a mixer with zirconium balls for 1-3 hours to prepare a mixture; (4) Melting: Place a crucible in a high-temperature electric furnace, add the mixture, raise the temperature to 850-1100°C according to the step temperature system, and keep it warm for 30-120 minutes to obtain clear glass liquid; (5) Crushing and grinding: The molten glass liquid is rolled in an open mill to cool to room temperature, then ground and sieved to obtain sealing glass powder; (6) Injection molding: The prepared sealing glass powder and the binder are mixed in a mass ratio of 4-5:1 in an internal mixer, and then pelletized or crushed to form feed material, which is then heated and injected into an injection molding machine to obtain a sealing glass green body; (7) Debonding: Soak the polished sealing glass blank in a solvent for 3-6 hours to remove the organic binder; (8) Vitrification sintering: The debonded sealing glass blank is vitrified and sintered in an inert gas atmosphere sintering furnace at 350-450°C. After keeping warm for 0.5-1.5 hours, it is cooled in the furnace. After sintering, the glass blank shrinks and takes shape, and finally a sealing glass blank is obtained.

6. The method for preparing a sealing glass blank for a power lithium battery according to claim 5, characterized in that: The particle size distribution of the sealing glass powder used in step (6) is D50: 60-80 μm, D99: 150-180 μm.

7. The method for preparing a sealing glass blank for a power lithium battery according to claim 5, characterized in that: The binder used in step (6) is an oil-soluble organic binder, which is one or more of ethyl cellulose, povidone, polyvinyl acetate, and polyvinyl acetal.

8. The method for preparing a sealing glass blank for a power lithium battery according to claim 5, characterized in that: The solvent used in step (7) is one or more of ethanol, ethyl acetate, acetone, chloroform, and xylene.

9. The method for preparing a sealing glass blank for a power lithium battery according to claim 5, characterized in that: The mixing temperature is 170-240°C, the injection temperature is 170-250°C, and the injection pressure is 12-30MPa.

Citation Information

Patent Citations

  • Lead-free low-melting sealing glass and preparation method thereof

    CN101597136A

  • Glass composition for electrode, paste for electrode using said glass composition, and electronic component using said paste

    CN103052605A

  • Glass blank powder injection molding process

    CN113429118A

  • Glass for bonding and sealing

    JP1995126037A

  • Lead-free and low-melting point glass and glass frit

    JP2001302279A